2018
DOI: 10.18517/ijaseit.8.2.3506
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of Record Statistics Based on Generalized Inverted Exponential Model

Abstract: In some situations, only observations that are more extreme than the current extreme value are recorded. This kind of data is called record values which have many applications in a lot of fields. In this paper, the Bayesian estimators using squared error and LINEX loss functions for the generalized inverted exponential distribution parameters are considered depending on upper record values and upper record ranked set sampling. The Bayes estimates and credible intervals are derived by considering the independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Studies about the GIE distribution were discussed by several researchers (for instance see [31][32][33][34][35]). Note that; for 1,  = the CDF (Equation ( 3)) reduces to the IE distribution.…”
Section: Model Specification and The Reliability Of The Structurementioning
confidence: 99%
“…Studies about the GIE distribution were discussed by several researchers (for instance see [31][32][33][34][35]). Note that; for 1,  = the CDF (Equation ( 3)) reduces to the IE distribution.…”
Section: Model Specification and The Reliability Of The Structurementioning
confidence: 99%
“…Combining the likelihood function in (6) and the conditional prior in (20), we get the conditional posterior of (β | α � α j ) as follows:…”
Section: Bayes Estimationmentioning
confidence: 99%
“…Record values appeared naturally in many real-life applications such as data relating to sport, weather, and lifetesting studies. Many authors studied record values and the associated statistics such as [1][2][3][4][5][6]. Furthermore, there are several studies which discussed some inferential methods based on record values for the Rayleigh [7,8], Weibull [9], inverse Weibull [10,11], exponentiated Family [12,13], Lomax [14,15], power Lindley model [16], exponentiated Weibull [17,18], and normal distribution [19].…”
Section: Introductionmentioning
confidence: 99%
“…for Bayesian comparison of record values based on generalized exponential distribution were considered in [2]. Also, authors found Bayesian analysis for record data Based on Generalized Inverted Exponential Model which considered in [3]. For finding interval estimation for Inverse Rayleigh Distribution based on lower record see [4].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2: MSEs OF MLE AND BAYES ESTIMATORS WHEN R=0.75 Shows that the MSEs of MLE and BAYES estimators decrease as n and m are increase at R=0.75, also, MSEs of MLE is smallest than MSEs of BayesFor Real data figures[3,4] …”
mentioning
confidence: 99%